Pre-exposure to Waterborne Nickel Downregulates Gastrointestinal Nickel Uptake in Rainbow Trout: Indirect Evidence for Nickel Essentiality - Chowdhury, M. Jasim; Bucking, Carol; Wood, Chris M (Environmental science & technology, 2008)
Nickel (Ni) may be both a toxicant and a micronutrient, but its essentiality to aquatic animals is not established. Interactions between branchial and gastrointestinal routes of metal uptake are important for understanding metal regulation and essentiality in aquatic animals. Adult rainbow trout (Oncorhynchus mykiss) were pre-exposed to a sublethal concentration of waterborne Ni (7.43 µmol L−1) or a control water (0.12 µmol L−1) for 45 days, and subsequently, a gastrointestinal dose of radiolabeled Ni (1.08 µmol kg−1 wet wt) was infused into the stomach of both non-pre-exposed and Ni pre-exposed trout to test whether pre-exposure to waterborne Ni would affect gastrointestinal uptake. The fish pre-exposed to waterborne Ni exhibited a markedly greater level of total Ni in the blood plasma (∼10-fold) but not in red blood cells (RBC). Pre-exposure downregulated the gastrointestinal uptake of radiolabeled Ni (new Ni) in the plasma and RBCs, providing evidence for the first time of homeostatic interaction between the two routes of Ni uptake. The plasma and RBC concentrations of new Ni in the non-pre-exposed and Ni pre-exposed groups were linear in the first 2 h and then approached a plateau. Only a small fraction of the infused dose (1.6–3.7%) was found in the internal organs of both groups at 24 h. Waterborne Ni, but not the infused Ni, greatly increased total Ni levels in the gills (6.1 fold), kidney (5.6 fold), scales (4.2 fold), and gut tissues (1.5–4.2 fold). It appears that gut, kidney and scales play important roles for Ni homeostasis by providing uptake, clearance and storage sites. Overall, our results suggest that Ni is subject to homeostatic regulation in the rainbow trout, a property that is characteristic of essential metals.